White matter connections reflect changes in voluntary-guided saccades in pre-symptomatic Huntington's disease - Klöppel, Stefan; Draganski, Bogdan; Golding, Charlotte V.; Chu, Carlton; Nagy, Zoltan; Cook, Philip A.; Hicks, Stephen L.; Kennard, Christopher; Alexander, Daniel C.; Parker, Geoff J. M.; Tabrizi, Sarah J.; Frackowiak, Richard S. J. (Brain (London, England : 1878), 2008)
Huntington's disease is caused by a known genetic mutation and so potentially can be diagnosed many years before the onset of symptoms. Neuropathological changes have been found in both striatum and frontal cortex in the pre-symptomatic stage. Disruption of cortico-striatal white matter fibre tracts is therefore likely to contribute to the first clinical signs of the disease. We analysed diffusion tensor MR image (DTI) data from 25 pre-symptomatic gene carriers (PSCs) and 20 matched controls using a multivariate support vector machine to identify patterns of changes in fractional anisotropy (FA). In addition, we performed probabilistic fibre tracking to detect changes in ‘streamlines’ connecting frontal cortex to striatum. We found a pattern of structural brain changes that includes putamen bilaterally as well as anterior parts of the corpus callosum. This pattern was sufficiently specific to enable us to correctly classify 82% of scans as coming from a PSC or control subject. Fibre tracking revealed a reduction of frontal cortico-fugal streamlines reaching the body of the caudate in PSCs compared to controls. In the left hemispheres of PSCs we found a negative correlation between years to estimated disease onset and streamlines from frontal cortex to body of caudate. A large proportion of the fibres to the caudate body originate from the frontal eye fields, which play an important role in the control of voluntary saccades. This type of saccade is specifically impaired in PSCs and is an early clinical sign of motor abnormalities. A correlation analysis in 14 PSCs revealed that subjects with greater impairment of voluntary-guided saccades had fewer fibre tracking streamlines connecting the frontal cortex and caudate body. Our findings suggest a specific patho-physiological basis for these symptoms by indicating selective vulnerability of the associated white matter tracts.